Clival Pituitary Adenoma with Acromegaly: Case Report and Review of Literature - Bhatoe, Harjinder S. (Thieme Medical Publishers, 2007)
The pituitary develops as a result of complex, intricate, and precise neuro-embryological events in the sixth to eighth weeks of gestation. Some ectopic cell rests can become adenomatous. Rarely, these cell rests in the clivus can be the site of formation of adenoma. Our patient, a 35-year-old parous woman, was being treated for acromegaly, and imaging studies revealed a clival mass lesion. Trans-sphenoidal excision was done and immunohistochemistry revealed the tumor to be a growth hormone-secreting tumor.